Aerosol Inhalation of Heat-Killed Clostridium butyricum CGMCC0313-1 Alleviates Allergic Airway Inflammation in Mice - Laodong Li; Qixiang Sun; Huan Xiao; Qiannan Zhang; Siyue Xu; Lejin Lai; Zhengning Li; Chaoqian Li (Journal of Immunology Research)
Epidemiological studies have shown that exposure to beneficial microorganisms can reduce the risk of asthma, but the clinical use of live probiotics is controversial due to the risk of infection. As heat-killed probiotics can also exhibit immunomodulatory activity, this study is aimed at investigating whether heat-killed Clostridium butyricum (HKCB) CGMCC0313-1 could reduce allergic airway inflammation in an ovalbumin-induced mouse model. Mice received aerosol inhalation of HKCB, oral administration of HKCB, or oral administration of live Clostridium butyricum (CB) during sensitization. Bronchoalveolar lavage fluid cell number, histology, and levels of the cytokines interferon-gamma and IL-4, the autophagy-related proteins LC3B, Beclin1, and p62, and members of the nuclear factor kappa B (NF-κB)/NLRP3 inflammasome signaling pathway were examined. Our results demonstrated that aerosol inhalation of HKCB, oral HKCB administration, and oral live CB administration alleviated allergic airway inflammation and mucus secretion in allergic mice. Aerosol inhalation of HKCB was the most effective method; it restored the Th1/Th2 balance, ameliorated autophagy, and inhibited the NF-κB/NLRP3 inflammasome signaling pathway in the lungs of allergic mice. Thus, aerosol inhalation of HKCB could be a promising strategy for the prevention or treatment of asthma.